Analisis Hubungan Body Girth Ikan Tongkol (Euthynnus affinis) dan Mesh Size Purse Seine Di Perairan Sibolga - Ratu Sari Mardiah; Kalvin Paiki; Shiffa Febyarandika Shalichaty (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
The main construction of the purse seine is wings, body and bag. The mesh size of each part is different. The wings have a mesh size of 10.16 cm, body 7.62 cm and bag 2.54 cm. Mesh size greatly affects the size of catch. Fish morphometric which is strongly influenced by mesh size is fish body girth. A mesh size larger than the body girth will allow fish to escape from the net and a smaller mesh size will trap fish by gilled, snagged or wedged. The purpose of the study was to distribute the frequency of the length and body girth of mackerel, analyze the relationship between length, body girth and mesh size of the purse seine. The research method used is experimental fishing for 2 trips. Analysis of the data used is linear regression, the formula for the width of the purse seine mesh opening and determination of body girth coefficient based on mesh size. The results showed that the minimum value of mackerel length was 35 cm and the maximum value was 57 cm. The highest length frequency distribution was at the size of 41-43 cm. The minimum value of fish body girth is 23 cm and the maximum value is 44 cm. The highest value in the body girth frequency distribution of fish was 29-31 cm. The relationship between length and body girth has a value of y=0.72x–1.91. The correlation value of body girth and mesh size is 0.82 and has an average body girth coefficient of 0.084 in the bag, 0.251 body and 0.335 wings. The fish body girth coefficient value is smaller than the standard. This means that mackerel caught tend to be wedged in the wings, gilled in the body and snagged in the bag.Key Words: Body Girth; Mackerel; Mesh Size; Purse Seine